Maximizing Longevity and Healthspan: Multiple Approaches All Converging on Autophagy - Bareja, Akshay; Lee, David E.; White, James P. (Frontiers in Cell and Developmental Biology, 2019)
Our understanding of the molecular basis of aging has greatly increased over the past few several decades. In this Review, we provide an overview of the key signaling pathways associated with aging, and whose modulation has been shown to extend lifespan in a range of model organisms. We also describe how these pathways converge onto autophagy, a catabolic process that functions to recycle dysfunction cellular material and maintains energy homeostasis. Finally, we consider various approaches of therapeutically modulating these longevity pathways, highlighting exercise as a potent geroprotector.